Surgical Outcome of Intraocular Lens Implantation in Children with Bilateral Developmental Cataract - Kumar Biswas, Sujit; Gani Chowdhury, Nasimul; Alam, Wahid; Hossain, Dostogir; Noor, Jannatun; Atika Islam, Urmi (BOHR International Journal of Current Research in Optometry and Ophthalmology, 2022)
Purpose: To evaluate the visual outcome and long-term complications of intraocular lens implantation along with primary posterior capsulectomy & anterior vitrectomy in children with bilateral developmental cataract. Methods: This retrospective study was carried out on the 48 eyes of 24 children who had undergone cataract surgery under general anesthesia. Age range was 2 to 8 years. All patients underwent primary posterior capsulectomy, primary in-bag intraocular lens (IOL) implantation, irrigation-aspiration of lens debris, and anterior vitrectomy. At intervals of one week, one month, three months, and six months, every case was evaluated. After 6 months best corrected visual acuity was recorded and intraocular pressure, anterior chamber angle, optic disc, and peripheral retina were evaluated. Results: Postoperative best corrected visual acuity were 6/6 in 10.4% eyes, 6/9-6/18 in 56.3% and <6/18 in 33% eyes. Intra ocular pressures were found within normal limit (12 ± 2.09 mm of Hg) in all cases. Anterior chamber angle was normal in 44 eyes (91.7%). Peripheral retina and vitreous were normal in all cases. No significant Optic disc changes were noticed. The most common cause of decreased vision was amblyopia (79.2%) in the fellow eye due to delayed surgery. Conclusion: Amblyopia is the main cause of decreased visual recovery in children after cataract surgery. Surgical intervention in proper time results in good visual outcome.